2017
DOI: 10.1016/j.trd.2017.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key assumptions and differences in life cycle assessment studies of lithium-ion traction batteries with focus on greenhouse gas emissions

Abstract: The various studies that consider the life cycle environmental impacts of lithium-ion traction batteries report widely different results. This article evaluates the inventory data and results to identify the key assumptions and differences in the studies. To aid the identification, we compile the reported life cycle greenhouse gas emissions of batteries. The studies find production-related emissions in the range of 38-356 kg CO2-eq/kWh. One of the main sources of the large variations stems from differing assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 28 publications
1
87
1
Order By: Relevance
“…The electrode materials (eg, lithium nickel‐cobalt‐manganese oxide [NCM] cathode or lithium iron phosphate [FePO 4 ] cathode) have a lower influence on the greenhouse gas emissions of battery production . The greenhouse gas emissions of the storage system with current LiNCM batteries modelled in this study amount to 185 kgCO 2 ‐eq/kWh and are therefore about in the middle of the range of previous publications, which spans from 38 to 356 kgCO 2 ‐eq/kWh . Only one study was found that quantified the environmental impacts of a stationary battery storage system used in a hybrid power plant consisting of a wind park, a PV system, and several diesel generators .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The electrode materials (eg, lithium nickel‐cobalt‐manganese oxide [NCM] cathode or lithium iron phosphate [FePO 4 ] cathode) have a lower influence on the greenhouse gas emissions of battery production . The greenhouse gas emissions of the storage system with current LiNCM batteries modelled in this study amount to 185 kgCO 2 ‐eq/kWh and are therefore about in the middle of the range of previous publications, which spans from 38 to 356 kgCO 2 ‐eq/kWh . Only one study was found that quantified the environmental impacts of a stationary battery storage system used in a hybrid power plant consisting of a wind park, a PV system, and several diesel generators .…”
Section: Resultsmentioning
confidence: 74%
“…38 The greenhouse gas emissions of the storage system with current LiNCM batteries modelled in this study amount to 185 kgCO 2 -eq/kWh and are therefore about in the middle of the range of previous publications, which spans from 38 to 356 kgCO 2 -eq/kWh. 38 Only one study was found that quantified the environmental impacts of a stationary battery storage system used in a hybrid power plant consisting of a wind park, a PV system, and several diesel generators. 39 The greenhouse gas emissions of the production of the analysed battery with a lithium nickel cobalt oxide cathode and a lithium titanate anode amount to approximately 290 kgCO 2 -eq/ kWh and are therefore significantly higher compared with the present study.…”
Section: Pv Systemmentioning
confidence: 71%
“…Several changes were made to this original inventory to represent the consequential methodology and the intended perspective and to integrate newly available data (Ellingsen et al. ; Peters and Weil ).…”
Section: Methodsmentioning
confidence: 99%
“…The inventory of the battery direct life cycle was based on data collected at an earlier stage of this research project (Vandepaer et al 2017). Several changes were made to this original inventory to represent the consequential methodology and the intended perspective and to integrate newly available data (Ellingsen et al 2017;Peters and Weil 2017).…”
Section: Battery and Components: Manufacturing And Transportmentioning
confidence: 99%
“…Estimates of energy usage and greenhouse gas (GHG) emissions associated with producing lithium-ion (Li-ion) batteries have been shown to vary considerably (Ellingsen et al 2017, Peters et al 2017, Romare and Dahllöf 2017. Energy requirements related to the mining and processing of raw materials appear to be in reasonable agreement between studies (Dunn et al 2014), while energy used for module or pack assembly is considered to require only minimal amounts of energy (Dai et al 2019), leaving the cell manufacturing processes as the largest source for the variation.…”
Section: Introductionmentioning
confidence: 99%